Gastrointestinal digestion of food proteins: Anticancer, antihypertensive, anti-obesity, and immunomodulatory mechanisms of the derived peptides - Yan, Zheng; Gui, Yang; Liu, Chunhong; Zhang, Xiaohai; Wen, Chaoling; Olatunji, Opeyemi Joshua; Suttikhana, Itthanan; Ashaolu, Tolulope Joshua (Food research international, 2024)
Food proteins and their peptides play a significant role in the important biological processes and physiological functions of the body. The peptides show diverse biological benefits ranging from anticancer to antihypertensive, anti-obesity, and immunomodulatory, among others. In this review, an overview of food protein digestion in the gastrointestinal tract and the mechanisms involved was presented. As some proteins remain resistant and undigested, the multifarious factors (e.g. protein type and structure, microbial composition, pH levels and redox potential, host factors, etc.) affecting their colonic fermentation, the derived peptides, and amino acids that evade intestinal digestion are thus considered. The section that follows focuses on the mechanisms of the peptides with anticancer, antihypertensive, anti-obesity, and immunomodulatory effects. As further considerations were made, it is concluded that clinical studies targeting a clear understanding of the gastrointestinal stability, bioavailability, and safety of food-based peptides are still warranted.
Keywords: Gastrointestinal Microbiome; Humans; Digestion; imunomodulační látky; Antineoplastic Agents; biologická dostupnost; Anti-Obesity Agents; Antihypertensive Agents; lidé; zvířata; dietní proteiny; peptidy; Peptides; Biological Availability; imunologické faktory; trávení; Immunologic Factors; protinádorové látky; střevní mikroflóra; Animals; Immunomodulating Agents; antihypertenziva; látky proti obezitě; Dietary Proteins; Gastrointestinal Tract; gastrointestinální trakt